A Practical Physical-Layer Network Coding with Spatial Modulation in Two-Way Relay Networks. (21st June 2017) - Jung, Bang Chul; Sook Yoo, Jae; Lee, Woongsup
Abstract: In this paper, we consider a two-way relay network consisting of a single relay node and two source nodes, where both the relay node and source nodes are equipped with multiple antennas. Two source nodes are assumed to transmit data with spatial modulation (SM) and the relay node is assumed to try to decode the network-coded packet (via bit-wise exclusive OR operation) of the two packets received from two source nodes, respectively. We propose a maximum-likelihood (ML) signal detection technique for the physical-layer network coded packet with SM for the relay node. Extensive simulation results show that the bit-error rate (BER) at the relay node becomes significantly improved with the proposed SM-based physical-layer network coding (PNC) technique, compared with the conventional PNC technique that achieving the same data rate. In particular, the performance of the proposed technique becomes excellent when the number of antennas at the nodes is large and the data rate is high, which implies that the proposed technique is suitable for the next-generation wireless communication system, i.e. 5G. Note that the proposed SM-based PNC technique does not require channel state information at transmitter (CSIT) and thus it can be implemented easily in practice.